1997
DOI: 10.1002/bies.950190412
|View full text |Cite
|
Sign up to set email alerts
|

DNA turnover and mutation in resting cells

Abstract: There is growing evidence that mutations can arise in non-dividing cells (both bacterial and mammalian) in the absence of chromosomal replication. The processes that are involved are still largely unknown but may include two separate mechanisms. In the first, DNA lesions resulting from the action of endogenous mutagens may give rise to RNA transcripts with miscoded bases. If these confer the ability to initiate DNA replication, the DNA lesions may have an opportunity to miscode during replication and thus coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 39 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…It is possible that phenol disturbs the DNA turnover in starving colR mutant bacteria. Indeed, studies of the stationary-phase (adaptive) mutation have revealed that a remarkable DNA turnover is needed for the emergence of mutations in starving populations of bacteria (6). As both transposition and point mutations require DNA synthesis, inhibition of DNA replication by phenol overdose should explain the suppression of mutational processes in starving bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that phenol disturbs the DNA turnover in starving colR mutant bacteria. Indeed, studies of the stationary-phase (adaptive) mutation have revealed that a remarkable DNA turnover is needed for the emergence of mutations in starving populations of bacteria (6). As both transposition and point mutations require DNA synthesis, inhibition of DNA replication by phenol overdose should explain the suppression of mutational processes in starving bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Of these DNA-insulting processes, those causing oxidative damage have been shown to be significant in B. subtilis cells under conditions of starvation (45). The ability of RNA polymerase to bypass these and perhaps other types of lesions may result in base misinsertion in the transcript, generating mutant proteins resulting in the appearance of pseudo-prototrophs in nondividing cells (4,22,37). This process was shown to occur in nondividing E. coli cells, where Bregeon et al demonstrated that RNA polymerase can efficiently bypass uracil and 8-oxoG lesions engineered into a luciferase reporter gene (3).…”
Section: Vol 192 2010 Stress-induced Mutagenesis In B Subtilis Celmentioning
confidence: 99%
“…Differences in the spectra of mutations have been observed between sets of mutants appearing in starving bacterial populations under selective conditions and in actively growing bacterial cultures (22,32,52,55). The starvation conditions encountered during stationary-phase incubation may permit a transient increase in the mutation rate due to a variety of factors, including decreased fidelity during replication and reduction of DNA repair activity (9,18,58,65; see also references in reference 21). Another mechanism that may increase genetic diversity is the movement of transposable elements (14,56).…”
mentioning
confidence: 99%